Exploring Antiparasitic Molecule Sources from Timber by-Product Industries—Leishmanicidal and Trypanocidal Compounds from Clathrotropis brunnea Amshoff - Torres, Fernando; Robledo, Sara M.; Quiñones, Wiston; Escobar, Gustavo; Archbold, Rosendo; Correa, Edwin; Gil, Juan Fernando; Arbeláez, Natalia; Murillo, Javier; Echeverri, Fernando (Frontiers in Pharmacology, 2020)
Through bioguided in vitro assays, the leishmanicidal and trypanocidal effects of an ethanol extract, seven fractions, and two pure substances obtained from Clathrotropis brunnea Amshoff sawdust were established. The effectiveness of the two metabolites was confirmed in a hamster model of cutaneous Leishmaniasis by Leishmania braziliensis and in Balb/c mice infected by Trypanosoma cruzi. In vitro, 3,5-dimethoxystilbene was the most active against L. braziliensis amastigotes, with a median lethal concentration (LC50) of 4.18 g/mL(17.40  and a selectivity index (SI) of 3.55, but showed moderate activity for T. cruzi, with a median effective concentration (EC50) value of 27.7 g/mL (115.36  . Flavanone pinostrobin, meanwhile, showed high activity against L. braziliensis, with an EC50 of 13.61 g/mL (50,39 , as well as for T. cruzi, with an EC50 of 18.2 g/mL (67.38 . The animal model assay of cutaneous Leishmaniasis showed that 50% of the hamsters treated with pinostrobin were definitively cured the cutaneous ulcer, and 40% showed an improvement, with a reduction in the size of the of 84%–87%. Moreover, Balb/c mice experimentally infected with T. cruzi and treated for 25 days with pinostrobin experienced a reduction in their parasitemia by 71%. These results demonstrate the high potential of C. brunnea Amshoff against cutaneous Leishmaniasis and American trypanosomiasis and indicate the pharmacological potential of waste from the wood industry, which has tons of potentially useful chemicals for the development of new medicines.